Firm Financial Performance in The Global 1000: Does Human Capital Effectiveness Matter? - Raghubeer, Sandhia (School of Management Studies, 2019)
Organisations worldwide spend a substantial proportion of revenue on salaries and benefits (compensation) as an investment in employees who are regarded as human capital. The justification behind this investment is the theoretical assertion that investments in human capital predict financial performance but empirical support for this relationship is limited. The present study contributes to the extant literature by examining the relationship between human capital effectiveness (HCE) and financial performance. A further contribution of the research is to consider alternative criteria of financial performance as findings may be dependent on operationalisation of the criterion. The relationships we tested were between Human Capital Return on Investment (HCROI) and (1) Return on Assets and (2) Return on Equity. Drawing on the Resource Based View theory, we conducted a study using 10 years of data from a sample that comprised the Global 1000 (highest revenue, listed firms domiciled across 45 countries). We used a retrospective correlational study. Spearman Correlation (rs) analysis revealed significant effects for the relationships we investigated in all years. Moreover, meta-analysis showed these effects to be significant on average across the 10 years, showing moderate strength and relative stability. A corollary of the study is that we established global benchmarks for HCROI and provided the first empirical evidence that supports a positive relationship between HCE and financial performance. These findings may be useful to investors who seek possible indicators of expected financial performance from HCE. In doing so, the study suggests we should expand financial reporting to include HCE indicators. Implications of findings and study limitations are noted.